The dynamics of brand equity, co-branding and sponsorship in professional sports. (2nd December 2009) - Frederick, Howard; Patil, Sandeep
Globalisation has been one of the most significant determinants of growth in the sports industry worldwide, especially with the increasing importance of brand creation, brand awareness, brand image, brand identity and brand equity. Professional sports teams have become top sports brands through leverage with major company sponsors. Sports marketers have had to become much more entrepreneurial to create competitive advantage for sports organisations and deliver relationship value to consumers. Company sponsorships are prominent drivers of brand strategy around the world. They help create an extended consumer experience and are becoming a strategic vehicle for creating co-branding partnerships between sports organisations and multinational companies. This study reports data from a survey of the top marketing and communications executives in sports and company organisations in New Zealand and as well as a qualitative content analysis of core documents and websites. The study provides insights for sports marketers seeking to: use sponsorship as a prominent driver of brand strategy; employ co-branding as a strategy to create an extended consumer experience; build strong brands through efficient co-branding articulation strategies. The study also provides recommendations for sports organisations and companies to formulate their marketing communications and brand strategies from the perspective of a co-branding relationship.